Teknik sambung mikro in vitro kina Cinchona succirubra dengan C. ledgeriana In vitro micrografting technique of Chincona succirubra and C. ledgeriana - Nurita TORUAN-MATHIUS; . LUKMAN; . AGUS-PURWITO (Menara Perkebunan, 2006)
Summary In vitro micrografting is a technique for grafting scions to rootstocks of plantlets from tissue culture. In vitro micrografting of Cinchona plant has never been carried out. The objective of this research was to obtain the best method of in vitro micrografting, medium for micrografted plantlets, and acclimatization  for Cinchona plantlets from  micrografting. The research consisted of (i) optimization of micrografting method, (ii) optimization of medium for growing plantlets, and (iii) acclimatization of micrografted plantlet. Plantlets of four-month-old of  C. ledgeriana  QRC clone were used as  scions, while of C. succirubra as  rootstocks. Each of experiments was arranged according to Completely Randomized Design, consisted of  combination of scion and rootstock and type of micro-grafting with 10 replicates. Parameters measured were  the percentage of survived plantlet, leaf number, and callus productions on union area, and percentage of survived  plantlet. The results show that V type of micrografting was the best for Cinchona micrografting. MS medium with the addition of 3 mg/L IBA was the best medium for growing of micrografted plantlet. Husk charcoal mixed with top soil (1 : 1) was the best medium for acclimatization.  Acclimatization  consisted  of two steps: preaclimatization in a culture room with 12- hour photoperiod at temperature 25 – 27oC  for two weeks,  followed by aclimatization in a plastic house with  70% reduced light intensity for one month. Using this method, 90% of the seedlings were survived. It is concluded that in vitro micrografting can be used as a technique for clonal propagation of Cinchona sp.Ringkasan  Teknik sambung mikro (mikrografting) in vitro adalah teknik penyambungan potongan batang atas pada batang bawah dalam kultur jaringan.  Pada tanaman kina teknik sambung mikro  in vitro belum pernah dilakukan. Tujuan penelitian ini adalah  menetapkan tipe sambung mikro, medium terbaik untuk planlet hasil sambung  mikro, dan perbanyakan tanaman kina dengan sambung mikro. Pelaksanaan percobaan meliputi (i) optimasi tipe sambung, (ii) optimasi  medium, dan (iii) aklimatisasi planlet hasil sambung mikro. Bahan tanaman yang digunakan sebagai batang atas adalah planlet Cinchona ledgeriana klon QRC, sedangkan sebagai batang bawah digunakan planlet  C. succirubra, berumur empat bulan. Masing- masing percobaan disusun dengan Rancangan Acak Lengkap terdiri dari dua taraf yaitu  kombinasi batang bawah dengan batang atas bentuk sambung tipe V dan L dilakukan  dengan 10 ulangan. Peubah yang diukur meliputi persentase planlet yang bertahan hidup,  jumlah daun,  berkalus atau tidak berkalus pada daerah pertautan, dan persentase planlet yang bertahan hidup. Hasil yang diperoleh menunjukkan bahwa tipe V merupakan cara sambung  mikro  yang terbaik. Medium MS dengan penambahan 3 mg/L IBA adalah medium terbaik untuk pertumbuhan dan perakaran planlet hasil sambung mikro.  Aklimatisasi planlet dilakukan dengan medium tumbuh arang sekam : top soil (1 : 1) yang disterilkan. Tahapan aklimatisasi adalah pre-aklimatisasi dalam ruang kultur  suhu 25 -     27 oCdengan pencahayaan 12 jam per hari dan diikuti dengan aklimatisasi di rumah plastik bernaungan 70% paranet. Dengan metode aklimatisasi ini  90% dari bibit mampu bertahan hidup. Kesimpulan dari penelitian ini menunjukkan bahwa teknik sambung mikro dapat digunakan untuk perbanyakan klonal   Cinchona sp..